Insufficient Post-operative Energy Intake Is Associated With Failure of Enhanced Recovery Programs After Laparoscopic Colorectal Cancer Surgery: A Prospective Cohort Study - Liu, Shuang; Zhang, Sheng; Li, Zike; Li, Meng; Zhang, Yujie; He, Min; Jin, Chengcheng; Gao, Chun; Gong, Jianping (Frontiers in Nutrition, 2021)
Background: Although enhanced recovery after surgery (ERAS) has been proven to be beneficial after laparoscopic colorectal surgery, some of the patients may be fail to complete ERAS program during hospitalization. The aim of this prospective study is to evaluate the risk factors associated with ERAS failure after laparoscopic colorectal cancer surgery. Methods: This is a prospective study from a single tertiary referral hospital. Patients diagnosed with colorectal cancer who met the inclusion criteria were included in this study. Demographic and clinicopathological characteristics were collected. Postoperative activity time and 6-mintue Walking Distance (6MWD) were measured. Patients were divided into ERAS failure group and ERAS success according to decreased postoperative activity and 6MWD. Factors associated with ERAS failure were investigated by univariate and multivariate analysis. Results: A total of 91 patients with colorectal cancer were included. The incidence of ERAS failure is 28.6% among all patients. Patients in ERAS failure group experienced higher rate of postoperative ileus and prolonged hospital stay (p<0.001). Multivariate analysis revealed that older age(p=0.006), BMI≥25.5 kg/m2 (P=0.037), smoking(p=0.002), operative time (P=0.048) and postoperative energy intake<18.5 kcal/ kg• d (P=0.045) were independent risk factors of ERAS failure after laparoscopic colorectal surgery. Conclusions: Our findings indicated that proportion of patients may fail the ERAS program after laparoscopic colorectal surgery. We for the first time showed that postoperative energy intake was an independent risk factor for ERAS failure. This may provide evidence for further investigation on precise measurement of nutritional status and selected high-risk patients to for enhanced nutrition support.